Chirped‐Pulse and Cavity‐Based Fourier Transform Microwave Spectra of the Methyl Lactate⋅⋅⋅Ammonia Adduct1. Issue 16 (14th March 2013) - Thomas, Javix; Sukhorukov, Oleksandr; Jäger, Wolfgang; Xu, Yunjie
<x xml:space="preserve">Abstract</x> Internal rotations: Using a broadband chirped‐pulse and a cavity‐based microwave spectrometer, the delicate balance between intra‐ and intermolecular hydrogen‐bonding interactions in the methyl lactate⋅⋅⋅NH3 adduct was investigated (see picture). The adduct is a prototype lock‐and‐key system consisting of a lock with two "spinning" tops and a key which is also a spinning top itself.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>